2016
DOI: 10.7860/jcdr/2016/17476.7278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotypic and Phenotypic Methods for Detection of Methicillin Resistant Staphylococcus aureus in a Tertiary Care Hospital of Eastern Odisha

Abstract: Introduction: Methicillin resistant Staphylococcus aureus has emerged as an important pathogen in nosocomial and community acquired infections. Accurate and rapid identification of MRSA in clinical specimens is essential for timely decision of effective antimicrobial chemotherapy. Aim:The present study was conducted to compare efficacy of four conventional phenotypic methods, with mec-A based polymerase chain reaction (PCR) for MRSA identification. materials and methods: Methicillin resistance was determined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
12
1
3
Order By: Relevance
“…Our finding was also in consideration with various other author's findings. 21,22 Rural population was at more risk for nasal carriage among HIV seropositive patients (statistically non significant) in the present study. Females (20.97%) account for more (statistically non significant) nasal carriage MRSA as compared to males (14.71%).…”
Section: Discussioncontrasting
confidence: 46%
“…Our finding was also in consideration with various other author's findings. 21,22 Rural population was at more risk for nasal carriage among HIV seropositive patients (statistically non significant) in the present study. Females (20.97%) account for more (statistically non significant) nasal carriage MRSA as compared to males (14.71%).…”
Section: Discussioncontrasting
confidence: 46%
“…Ostojić & Hukić (2015) demonstrated a correlation between phenotypic and genotypic characteristics. Their results revealed that all MrSA isolates were mecA + , while Panda et al (2016) stated that using conventional methods for detection of MrSA is more significant than detection with PCR. In the present study, 15.6% (n= 8) isolates showed low level of resistance to oxacillin (1 or 2μg/ml) were found to harbor mecA gene, while four isolates that were resistant to ≥4μg/ml oxacillin lacked mecA gene.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we developed the npcRNA based detection using Sau-02 gene. Most of the detection studies carried out qualitatively to show the presence or absence of MRSA [ 36 , 39 , 40 ]. However, in our study we showed the detection level of genomic DNA equivalent to genome copies and whole cell MRSA as ~10 and 2 respectively.…”
Section: Resultsmentioning
confidence: 99%